Kontra Narasi Terorisme Dalam Syair Arab: Kajian Syair Karya Muhammad bin Rasyid Ali Maktum - Khulqi, Aghnin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
Until now, terrorism is still a big problem in society. That is why it is very necessary to carry out movements to counter acts of terrorism. One way to overcome this is by carrying out a counter-narrative of terrorism, namely by compiling a narrative that is deliberately created and framed with the aim of countering or minimizing the influence of negative narratives that have an intolerant and extreme tone. Sheikh Muhammad bin Rasyid Ali Maktum is a high-ranking official in the UAE who took part in carrying out a counter-narrative of terrorism in poetry. This study focuses on examining the counter-narrative in his poetry entitled Fitnah al-Irhab using a descriptive qualitative method that uses heuristic and hermeneutic reading of the poetry. This study resulted in the finding that the poem entitled Fitnah al-Irhab has fulfilled four steps or four points as a form of counter-narrative of terorism. Namely, first: reframing the conflict, second: counter analogy, third: counter strategic goals, and fourth: use rhetorical language style.Keywords - Terrorism, Counter Narrative, Arabic Poem, Muhammad bin Rasyid Ali Maktum.